Ultrasound-guided local methotrexate treatment for cesarean scar pregnancy in the first trimester: 12 years of single-center experience in China. (December 2019) - Li, Qiuyang; Xu, Hong; Wang, Yanqiu; Liu, Qin; He, Ping; Wang, Longxia
Abstract: Objective: To investigate the efficacy and safety of ultrasound-guided local injection of methotrexate (MTX) in the treatment of cesarean scar pregnancy (CSP) diagnosed in the first trimester. Study design: The clinical and imaging data of 101 CSP patients who received ultrasound-guided local injection of MTX in our hospital between January 2007 and December 2018 were retrospectively analyzed. The decline in serum β human chorionic gonadotropin (βHCG) level, size and blood flow of lesions, vaginal bleeding, liver/kidney functions, and other indicators were observed or tested after treatment on a weekly basis. Results: The duration of amenorrhea was 6.1 ± 0.8 weeks (range: 5.7–8.1 weeks) and the initial serum βHCG level was 20, 321 ± 965 U/L in 97 patients, The mean time t to βHCG normalization was 40 ± 14 days (range: 21–140 days), Minor intermittent vaginal bleeding occurred after local MTX injection, lasting 25 ± 17 days (range: 10–61 days), and the lesions at the scar sites had completely disappeared with an average interval of 39 ± 29 days ; The treatment failed in four patients. The average duration of amenorrhea was 7.5 weeks and the average initial serum βHCG level was 91, 359 U/L. Conclusion: Ultrasound-guided local injection of MTX is an effective and minimally invasive treatment for CSP. However, it is not feasible for patients with long-term amenorrhea (>8 weeks) and markedly increased blood βHCG level.